The Control of Fungus Uromycladium tepperianum on Seedling of Sengon (Falcataria moluccana (Miq.) Barneby & J.W.Grimes) in a nursery - Kurniawati Purwaka Putri; Yulianti Bramasto (Jurnal Perbenihan Tanaman Hutan, 2017)
Sengon (Falcataria moluccana (Miq. Barneby & J.W.Grimes) is one of timber producing species of high economic value. Recently, sengon productivity decreases due to pests and diseases, attack is caused by the fungus Uromycladium tepperianum (SACE.) McAlp. The control of gall rust disease at seedling level is important, because the stadia nursery are the most vulnerable. The aim of this research was to determine the effectiveness of the type of control in supressing the fungus of U. tepperianum and the growth of sengon in a nursery. The research design used a completely randomized design (CRD) with five treatments of gall rust disease control types i.e. control ; biological fertilizer of Plant Growth Promoting Rhizobacteria (PGPR) (5 g -L of water), biofungicide (5 g-L of water); chemical fungicide (2 g-L of water); and boron (300 ppm). Each treatment consisted of 20 seedlings repeated 4 times. The observed response were the number of fungal spores, diameter and height of seedlings. In addition, calculation of the effectiveness of the type of controller was counted. The results showed that after two weeks of fungal infections, the highest seedling growth was the seedling treated with fungicide (0.53 cm), while the lowest was the seedling treated with biological fungicide (0.32 cm). PGPR, fungicide biological, chemical fungicides and boron did not effective to the attack of fungus and to increase the growth of height and diameter of sengon seedling after the 4th week of the fungus infection.